Channels and countermeasures of the COVID-19 pandemic’s impact on urban economic resilience: Lessons from China - Xianxiang Lu; Yangrui Duan (PLoS ONE, 2025)
Resilience is a crucial ability of an economy to withstand sudden events and uncertain shocks. Using the entropy method, this study measures the economic resilience of 281 Chinese cities (prefecture-level and above) from 2017 to 2022, and empirically examines the impact of COVID-19 on this resilience, as well as its transmission channels. The results show that COVID-19 adversely affected overall urban economic resilience, with contrasting effects across its sub-dimensions: an insignificant negative impact on shock resistance, a significant negative impact on adaptive recovery, and an insignificant positive impact on innovative transformation. Transmission channels analysis reveals COVID-19 impaired urban economic resilience through the channels of employment structure, consumption, investment, and unrelated diversification, with consumption identified as the predominant one. Heterogeneity analysis reveals that the economic resilience of cities in both the high and low manufacturing specialization groups was more adversely affected by COVID-19 than that of cities in the medium group. Regarding services specialization, the economic resilience of cities with a medium degree of services specialization were more negatively affected by COVID-19 than that of cities with low services specialization. Furthermore, the economic resilience of cities with a higher degree of related diversification was less negatively affected by COVID-19. This study provides a replicable analytical framework and empirical evidence for enhancing urban economic resilience in China and other countries in post-pandemic era.